110 Effect of different backgrounding diets for weaning beef calves on complete blood counts pre and post shipping. (29th July 2019) - Tigue, Daniel A; Wilkerson, Shannon R; Rehm, John G; Holland, Courteney M; Broadway, Paul R; Carroll, Jeffery A; Burdick-Sanchez, Nicole; Theurer, Miles; Rodning, Soren P; Starkey, Jessica D; Mullenix, Mary K; Bratcher, Christy L
Abstract: The objective of this study was to evaluate if diet during the background phase has an effect on complete blood counts as an indicator of the stress response and immune function of calves shipped to feedyards in western Kansas from the Southeast. One hundred twenty (n = 120) Angus- and Hereford-sired steers (n = 60, 237.9±21.6 kg BW) and heifers (n = 60, 227.6±17.9 kg BW) from the E.V. Smith Research Center in Shorter, AL, were weaned on June 14, 2018. The following day, calves were weighed and blood was collected for analysis. Calves were then held in drylots for 14 d until forages reached an adequate height to begin grazing. Calves were then stratified by weight and randomly assigned to four dietary treatments, with three pens per treatment: Grazing (G), Grazing with supplement (GS), dry hay with supplement (HS), or baleage with supplement (BS). Dried distiller's grains with solubles fed at 1% of BW was used in each diet including supplementation. After 80 d on treatment diets, calves were shipped to Hy-Plains Feedyard, LLC. in Montezuma, KS. Immediately prior to shipment, immediately post-shipment, and after 24 hr rest, blood was collected for analysis. Whole blood collected at each of the four times points was analyzed for complete blood counts using a ProCyte Dx Hematology Analyzer. The data were analyzed using the Mixed Procedure in SAS. While no significant differences (P > 0.05) were detected post-weaning and prior to initiation of dietary treatments, differences across diets were seen in red blood cell count, hemoglobin, hematocrit, reticulocyte count, platelet count, white blood cell count, neutrophil count, lymphocyte count, neutrophil to lymphocyte ratio, and basophil counts (P < 0.05). Results of this study show that post-weaning backgrounding diets can have an effect on immune response to shipping stress